The debate on the Crusades - Tyerman, Christopher (Issues in historiography, 2011)
"David Hume, the eighteenth century philosopher, famously declared that 'the crusades engrossed the attention of Europe and have ever since engaged the curiosity of man kind'. This is the first book length study of how succeeding generations from the First Crusade in 1099 to the present day have understood, refashioned, moulded and manipulated accounts of these medieval wars of religion to suit changing contemporary circumstances and interests. Modern perceptions of the crusade remain in many places vivid; in some malign and politically toxic. This book explores the literary and academic traditions that have framed past and present debate. The crusades have attracted some of the leading historical writers, scholars and controversialists from John Foxe (of Book of Martyrs fame), to the philosophers G.W. Leibniz, Voltaire and David Hume, to historians such as William Robertson, Edward Gibbon and Leopold Ranke. Academic trends and controversies in Europe, America and the Near East in the last hundred years, including discussions of all the leading modern crusader scholars from Carl Erdmann and Steven Runciman onwards, bring the account up to date in 2010. Accessibly written, a history of histories and historians, the book will be of interest to students and researchers of crusading history from sixth form to postgraduate level and beyond; to cultural historians of the use of the past and of medievalism; and to those generally concerned with how the crusades have retained their power to inflame, especially since 9/11."--Publisher's website